2021
DOI: 10.1111/hepr.13676
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis C virus on survival in patients undergoing resection of intrahepatic cholangiocarcinoma: Report of a Japanese nationwide survey

Abstract: Aim We reviewed the data of a nationwide follow‐up survey to determine the impact of hepatitis C virus (HCV) infection on the outcomes of hepatectomy for mass‐forming (MF) type, and combined mass‐forming and periductal infiltrating (MF + PI) type intrahepatic cholangiocarcinoma (ICC). Methods In total, 956 patients with ICC who underwent curative hepatic resection were included in this cohort study, and patients were classified according to virus status. Patients were classified according to virus status as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…There were seven studies with 1181 patients (HCV+ n = 205, HCV- n = 976)[ 11 , 17 - 22 ]. Kaibori et al [ 19 ] performed propensity score matching (PSM) analysis to derive their cohorts; only the PSM cohort was analysed in our study. Uenishi et al [ 20 ] performed univariate and multivariate analyses on the impact of HCV infection on outcomes of surgical resection in cholangiocarcinoma, of which outcomes of the multivariate analysis was included in our study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were seven studies with 1181 patients (HCV+ n = 205, HCV- n = 976)[ 11 , 17 - 22 ]. Kaibori et al [ 19 ] performed propensity score matching (PSM) analysis to derive their cohorts; only the PSM cohort was analysed in our study. Uenishi et al [ 20 ] performed univariate and multivariate analyses on the impact of HCV infection on outcomes of surgical resection in cholangiocarcinoma, of which outcomes of the multivariate analysis was included in our study.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies involving 294 patients (HCV+ n = 135, HCV- n = 159) which reported on RFS[ 19 , 20 ]. Meta-analysis was not performed for RFS due to the small sample size and limitations in interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICC is a heterogeneous disease, which results from accumulation of genetic and epigenetic alterations in tumor cells, microorganisms, and host immunity 1,32–35 . The mechanisms by which disability in perioperative ADL correlates with recurrence and mortality after resection of ICC are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The Japan Liver Cancer Association (formerly Liver Cancer Study Group of Japan) has worked to advance the study and treatment of liver cancer since 1969, carrying out 22 national surveys on primary liver cancer with institutional members and collaborating institutions across Japan based on its General Rules for the Clinical and Pathological Study of Primary Liver Cancer, 1–11 and publishing the official results of those surveys and original article using this database 12–54 , 55–97 ,. 98–107 The group also reports on the Response Evaluation Criteria in Cancer of the Liver 108–117 . Recently, the Japan Liver Cancer Association also published clinical practice guidelines for intrahepatic cholangitis carcinoma 107…”
Section: Introductionmentioning
confidence: 99%